Social Norms, Endogenous Sorting and the Culture of Cooperation - Ernst Fehr; Tony Williams (Institute of Labor Economics (IZA), 2018)
Throughout human history, informal sanctions played a key role in the enforcement of social norms and the provision of public goods. However, a considerable body of evidence suggests that informal peer sanctions often cause large efficiency costs. This raises the question whether alternative (peer) sanctioning systems exist that avoid these costs and will be preferred by the people. Here, we show that welfare-enhancing peer sanctioning without much need for costly punishment emerges quickly if we introduce two relevant features of social life into the experiment: (i) subjects can migrate across groups with different sanctioning institutions and (ii) they have the chance to achieve consensus about normatively appropriate behavior. The exogenous removal of the norm consensus opportunity reduces the efficiency of peer punishment and renders centralized sanctioning by an elected judge the dominant institution. However, if given the choice, subjects universally reject peer sanctioning without a norm consensus opportunity – an institution that has hitherto dominated research in this field – in favor of peer sanctioning with a norm consensus opportunity or an equally efficient institution with centralized punishment by an elected judge. Migration opportunities and normative consensus building are key to the quick emergence of an efficient culture of universal cooperation because the more prosocial subjects populate the two efficient institutions first, elect prosocial judges (if institutionally possible), and immediately establish a social norm of high cooperation. This norm appears to guide subjects' cooperation and punishment choices, including the virtually complete removal of antisocial punishment when judges make the sanctioning decision.
Keywords: D02; D03; D72; H41; 330; cooperation; punishment; endogenous institutions; public goods